The role of the central banks in regional integration: Analysing financial convergence initiatives led by the Central Bank of Brazil and the Reserve Bank of India towards a regional payment system in MERCOSUR and SAARC - Campos, Andre Sanches Siqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Central banks play a significant role in promoting regional economic, financial, and monetary cooperation by upgrading the payment and settlement systems. However, close coordination and cooperation require facilitating the implementation of reforms at domestic and cross-border levels in order to benchmark with international standards. This context tends to be influenced by the interests of developed countries and the dimensions of regulatory globalisation promoted by international bureaucracies such as the BIS, IMF, World Bank, UN Regional Commissions, and Regional Development Banks in global financial governance. This framework of political interactions shapes the behaviour of central banks, which may drive or constrain regional integration. This research aims to analyse the role of the Central Bank of Brazil and the Reserve Bank of India towards regional financial cooperation identifying instruments that foster, gridlock, or redefine cooperation, particularly within the framework of MERCOSUR and SAARC. Since the mid-2000s, these central banks have set financial convergence initiatives with the purpose of developing a regional payment system at MERCOSUR and SAARC, which facilitate intra-trade performance and enhance foreign direct investments and, consequently, improve expectations of deepening regional integration in South America and South Asia. This research contributes to Regional Integration studies by filling the gaps in the existing literature addressing how central banks provide an effective institutional arrangement for regional organizations to achieve political and economic objectives. This qualitative document analysis research is based on Rational Choice Institutionalism and supported by Historical Institutionalism to approach critical junctures. It approaches multiple sources of data based on central banks, national governments, and regional organizations supported by existing literature. Findings from empirical evidence of the selected case studies demonstrated that the central banks of Brazil and India tend to be reluctant to deepen regional integration because of the existing economic, political, and institutional asymmetries that shape their regions. Central banks strengthened regional financial cooperation initiatives as they reduced the economic risks implicit in the integration process, aiming to protect the stability of their national financial system, foster national development, and preserve the political autonomy of Brazil and India, which provides political ground for the contestation of the Global Financial Governance.

Os bancos centrais desempenham um relevante papel na promoção da integração econômica, financeira e monetária regional, aprimorando os sistemas de pagamento e liquidação. No entanto, para uma coordenação e cooperação regional mais profunda é necessário facilitar a implementação de reformas a nível nacional e regional, a fim de atender às normas estabelecidas pelos padrões internacionais. Este contexto tende a ser influenciado pelos interesses dos países desenvolvidos e pelas dimensões da globalização regulatória promovidas por burocracias internacionais como BIS, FMI, Banco Mundial, comissões regionais das Nações Unidas e bancos regionais de desenvolvimento no processo de governança financeira global. Essa estrutura de interação política molda o comportamento dos bancos centrais, o que pode impulsionar ou constranger a integração regional. O objetivo desta pesquisa é analisar o papel do Banco Central do Brasil e do Banco da Reserva da Índia em relação à cooperação financeira regional, identificando os instrumentos que incentivam, constrangem ou redefinem a cooperação, particularmente, no âmbito do MERCOSUL e da SAARC. Desde meados dos anos 2000, esses bancos centrais estabeleceram iniciativas de convergência financeira com o objetivo de desenvolver um sistema de pagamentos regional no MERCOSUL e SAARC, visando facilitar o desempenho do comércio intrabloco e potencializar os investimentos estrangeiros diretos, consequentemente, melhorando as expectativas de aprofundamento da integração regional na América do Sul e no Sul da Ásia. Esta pesquisa contribui para os estudos de Integração Regional ao preencher as lacunas na literatura existente abordando como os bancos centrais fornecem um arranjo institucional eficaz para organizações regionais atingirem objetivos políticos e econômicos. Trata-se de uma pesquisa qualitativa de análise documental baseada no Institucionalismo da Escolha Racional e apoiada pelo Institucionalismo Histórico na abordagem de conjunturas críticas. Esta pesquisa aborda múltiplas fontes de dados proveniente dos bancos centrais, dos governos nacionais e das organizações regionais, fundamentada na literatura acadêmica existente. Os resultados das evidências empíricas dos estudos de caso selecionados demonstraram que os bancos centrais de Brasil e Índia apresentam relutância em relação ao aprofundamento da integração regional devido às assimetrias econômicas, políticas e institucionais existentes na região. Os bancos centrais promoveram o avanço da cooperação financeira regional na medida em que reduziram os riscos financeiros implícitos no processo de integração, visando proteger a estabilidade dos sistemas financeiros nacionais, o alcance dos objetivos nacionais de desenvolvimento e a preservação da autonomia política de Brasil e Índia, o que proporcionou base política para a contestação da Governança Financeira Global.

Los bancos centrales desempeñan un papel relevante en la promoción de la integración económica, financiera y monetaria regional, mejorando los sistemas de pago y liquidación. Sin embargo, para una coordinación y cooperación regionales más profundas es necesario facilitar la implementación de reformas a nivel nacional y regional para cumplir con las normas establecidas por los estándares internacionales. Este contexto tiende a estar influenciado por los intereses de los países desarrollados y las dimensiones de la globalización regulatoria promovidas por burocracias internacionales como el BIS, el FMI, el Banco Mundial, las comisiones regionales de las Naciones Unidas y los bancos regionales de desarrollo en el proceso de gobernanza financiera global. Esta estructura de interacción política moldea el comportamiento de los bancos centrales, lo que puede impulsar o limitar la integración regional. El objetivo de esta investigación es analizar el papel del Banco Central de Brasil y del Banco de la Reserva de la India en relación a la cooperación financiera regional, identificando los instrumentos que alientan, limitan o redefinen la cooperación, particularmente en el ámbito del MERCOSUR y la SAARC. Desde mediados de la década de 2000, estos bancos centrales han establecido iniciativas de convergencia financiera con el objetivo de desarrollar un sistema de pagos regional en el MERCOSUR y la SAARC, com el propósito de facilitar el desempeño del comercio intrabloque y mejorar la inversión extranjera directa, mejorando en consecuencia las expectativas de profundización de la integración regional en América del Sur y el Sur de Asia. Esta investigación contribuye a los estudios de integración regional al llenar los vacíos en la literatura existente al abordar cómo los bancos centrales crean un arreglo institucional efectivo para que las organizaciones regionales logren objetivos políticos y económicos. Se trata de una investigación cualitativa de análisis documental basada en el Institucionalismo de Elección Racional y sustentada en el Institucionalismo Histórico en el abordaje de coyunturas críticas. Esta investigación aborda múltiples fuentes de datos de bancos centrales, gobiernos nacionales y organizaciones regionales, basadas en la literatura académica existente. Los resultados de la evidencia empírica de los estudios de caso seleccionados demostraron que los bancos centrales de Brasil e India son reacios a profundizar la integración regional debido a las asimetrías económicas, políticas e institucionales que existen en la región. Los bancos centrales promovieron el avance de la cooperación financiera regional en la medida en que redujeron los riesgos financieros implícitos en el proceso de integración, con el objetivo de proteger la estabilidad de los sistemas financieros nacionales, el logro de los objetivos de desarrollo nacional y la preservación de la autonomía política de Brasil y India, que proporcionó una base política para desafiar la Gobernanza Financiera Global.

Centrale banken kunnen een belangrijke rol spelen bij het stimuleren van regionale economische, financiële en monetaire samenwerking door het versterken van de betalings- en afwikkelingssystemen. Hervormingen op binnenlands en grensoverschrijdend niveau moeten vlot uitvoerbaar zijn om nauwe coördinatie en samenwerking mogelijk te maken. De hervormingen laten tevens toe te benchmarken met internationale normen. Deze context wordt meestal beïnvloed door de belangen van ontwikkelde landen en de dimensies van globalisering van regelgeving die worden bevorderd door internationale bureaucratieën zoals de BIS, het IMF, de Wereldbank, regionale commissies van de VN en regionale ontwikkelingsbanken in het mondiale financiële bestuur. Dit kader van politieke interacties geeft vorm aan het gedrag van centrale banken, dat regionale integratie kan stimuleren of afremmen. Dit onderzoek is gericht op het analyseren van de rol van de Centrale Bank van Brazilië en de Reserve Bank van India ten aanzien van regionale financiële samenwerking, waarbij instrumenten worden geïdentificeerd die samenwerking bevorderen, blokkeren of herdefiniëren, met name binnen het kader van MERCOSUR en SAARC. Sinds het midden van de jaren 2000 hebben deze centrale banken financiële convergentie-initiatieven genomen met als doel de ontwikkeling van een regionaal betalingssysteem in MERCOSUR en SAARC, wat de prestaties op het gebied van intra handel vergemakkelijkt en directe buitenlandse investeringen bevordert en daarmee de verwachtingen van een verdieping van de regionale integratie in Zuid-Amerika en Zuid-Azië verbetert. Dit onderzoek draagt bij aan studies over regionale integratie door de hiaten in de bestaande literatuur aan te vullen over hoe centrale banken een effectieve institutionele regeling vormen voor regionale organisaties om politieke en economische doelstellingen te bereiken. Dit is een kwalitatief document analyseonderzoek gebasseerd op Rational Choice Institutionalism en ondersteund door Historical Institutionalism dat kritieke momenten benadert. Het benadert meerdere bronnen op basis van centrale banken, nationale regeringen en regionale organisaties, ondersteund door bestaande literatuur. Bevindingen uit empirisch bewijs van de geselecteerde casestudies toonden aan dat de centrale banken van Brazilië en India doorgaans terughoudend zijn om de regionale integratie te verdiepen vanwege de bestaande economische, politieke en institutionele asymmetrieën die hun regio's vormgeven. De centrale banken versterkten de initiatieven voor regionale financiële samenwerking omdat ze de economische risico's verminderden die impliciet verbonden waren aan het integratieproces, met als doel de stabiliteit van hun nationale financiële systeem te beschermen, de nationale ontwikkeling te bevorderen en de politieke autonomie van Brazilië en India te behouden, wat een politieke basis vormt voor de betwisting van het mondiale financiële bestuur.
El papel de los bancos centrales en la integración regional: Análisis de las iniciativas de convergencia financiera lideradas por el Banco Central de Brasil y el Banco de la Reserva de la India hacia un sistema de pagos regional en el MERCOSUR y la SAARC
De rol van de centrale banken bij regionale integratie: analyse van financiële convergentie-initiatieven van de Centrale Bank van Brazilië en de Reserve Bank van India naar een regionaal betalingssysteem in MERCOSUR en SAARC
Keywords: SAARC; Brazil; India; Brasil; Brazilië; MERCOSUL; MERCOSUR; Central Banks; Bancos Centrais; Bancos Centrales; Centrale banken; Global Financial Governance; Governança Financeira Global; Gobernanza Financiera Global; Mondiale Financiële Bestuur; Payment System; Sistema de Pagamentos; Sistema de Pagos; Betalingssysteem; Regional Cooperation; Cooperação Regional; Cooperación Regional; Regionale samenwerking